2012
DOI: 10.1016/j.ijdevneu.2012.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated establishment of mature signaling patterns following stimulation of developing neuronal networks: “learning” versus “plasticity”

Abstract: Neuronal networks established on micro-electrode arrays provide useful models for synaptic plasticity. Whether or not this represents a facet of learning is debated since ex vivo networks are deprived of organismal interaction with the environment. We compared developmental signaling of such networks with and without stimulation with a prerecorded synaptic signal from another mature culture as a model of sensory input. Unstimulated networks displayed a developmental increase in individual signals that eventual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 10 publications
(42 citation statements)
references
References 45 publications
4
38
0
Order By: Relevance
“…Long‐term cultures ( i.e. , those maintained for ≥1–2 months) develop spontaneous, complex signals (termed “bursts” by convention) (Madhavan et al, 2007; Rolston et al, 2007; Wagenaar et al, 2006; Zemianek et al, 2012a) that resemble the bursting activity observed during development in situ (Ben‐Ari, 2001; Khazipov et al, 2004; Zhang and Poo, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Long‐term cultures ( i.e. , those maintained for ≥1–2 months) develop spontaneous, complex signals (termed “bursts” by convention) (Madhavan et al, 2007; Rolston et al, 2007; Wagenaar et al, 2006; Zemianek et al, 2012a) that resemble the bursting activity observed during development in situ (Ben‐Ari, 2001; Khazipov et al, 2004; Zhang and Poo, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This unique model can be analyzed in detail, and/or expanded upon to encompass additional functionality. Prior studies demonstrated that these networks display alterations in signaling consistent with long-term potentiation following repetitive stimulation with the same digitized synaptic signal utilized herein [4,6]. Embodiment of the neuronal network as described herein provides the unique opportunity for future studies of long-term potentiation by biological neuronal networks in an environmental context.…”
Section: Discussionmentioning
confidence: 82%
“…Signaling was recorded using a MEA-1060-INV amplifier over 30 second intervals and collected via a DT9814 acquisition system and a software program ("Raptor") developed in our laboratory [3,4] (available at https://github.com/ mtgjbird/Raptor). Raptor requires the LabView (National Instruments) run-time engine 2013 SP1 or later http://www.ni.com/download/labview-run-time-engine-2013-sp1/4540/en/.…”
Section: Recording Of Network Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the synaptic signal induced more robust development of neuronal networks in culture than those induced by higher voltage, artificial signals. 42 The findings herein suggest that stimulation with a synaptic signal, and perhaps, additional biological signals, may be useful in physical therapy to promote muscle regeneration/repair.…”
Section: Zemianek Et Almentioning
confidence: 77%